2017
DOI: 10.1097/shk.0000000000000814
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate

Abstract: Sepsis is an acute life-threatening multiple organ failure caused by a dysregulated host response to infection. Endothelial dysfunction, particularly barrier disruption leading to increased vascular permeability, edema, and insufficient tissue oxygenation, is critical to sepsis pathogenesis. Sphingosine-1-phosphate (S1P) is a signaling lipid that regulates important pathophysiological processes including vascular endothelial cell permeability, inflammation, and coagulation. It is present at high concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 77 publications
1
18
0
2
Order By: Relevance
“…Our findings are in line with several experimental and clinical studies reporting a drastic loss of S1P in experimental sepsis models in animals and also in patients with sepsis and septic shock [31]. A decreased amount of S1P in patients had the same predictive value for septic shock as the SOFA score [9].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are in line with several experimental and clinical studies reporting a drastic loss of S1P in experimental sepsis models in animals and also in patients with sepsis and septic shock [31]. A decreased amount of S1P in patients had the same predictive value for septic shock as the SOFA score [9].…”
Section: Discussionsupporting
confidence: 90%
“…EPCs originate from hemangioblast existing in peripheral blood or bone marrow [18] and express cell surface markers similar to those of mature ECs [19]. Endothelial damage is an important early step in the pathogenesis of AS [20]. It is suggested that impaired EPCs population can negatively affect the cardiovascular system, and a decreased quantity of EPCs in patients is associated with an increased risk for endothelial injury and a progression of AS plaque [3].…”
Section: Discussionmentioning
confidence: 99%
“…S1P can inhibit the adhesion of leukocytes to ECs and subsequent transmigration, as well as the production of proinflammatory mediators in ECs. In addition, it can activate eNOS [20]. S1P/S1P receptors/Src kinases/CXCR4 receptor-mediated signaling was essential for homing and functional integration of EPCs to ischemic tissues [14].…”
Section: Discussionmentioning
confidence: 99%
“…With these promising protective effects and its reduced levels in sepsis patients, S1P might be considered as a potential therapeutic target as well as biomarker for EC barrier dysfunction and sepsis. 106 The studies have established that activation of Rac and subsequent cytoskeletal remodeling is the major intracellular signaling pathway that mediates the beneficial effects of S1P on pulmonary EC. 95,107,108 The pathways activated by S1P upstream of Rac include PI3K, Src, and elevation of intracellular calcium concentration.…”
Section: Sphingosine-1-phosphatementioning
confidence: 99%